Design and Evaluation of Delayed-Release Osmotic Capsule of Acetaminophen: Delayed-release osmotic capsule of acetaminophen - Barzegar-Jalali, Mohammad; Siyahi-Shadbad, Mohammad Reza; Barzegar-Jalai, Azim; Adibkia, Khosro; Mohammadi, Ghobad; Aghai, Behnaz; Zeraati, Mahdi (Iranian Journal of Pharmaceutical Sciences, 2006)
Hard gelatin capsule filled with acetaminophen, osmotic agent (sorbitol), a release promoter (sodium dodecyl sulfate), coated with a semipermeable cellulose acetate membrane containing a hydrophobic plasticizer (castor oil) and sealed with white bees wax plug was designed. When placed in the sink water penetrates the membrane, dissolves the osmotic agent and increases the osmotic pressure inside the capsule. The increased osmotic pressure enhances the water imbibition and consequently increases the hydrostatic pressure inside the capsule and when the latter pressure is high enough it expels out the plug and the drug release commences. With cellulose acetate concentration constant in membrane forming solution, 11% (w/w), the factors affecting the onset of the drug release, i.e. the lag time (tL), were thickness of semipermeable membrane (0.033-0.112 mm) and plug thickness (2.40-3.40 mm) although the influence of semipermeable membrane thickness was more important than plug thickness in delaying the onset of release. As the statistical analysis revealed, castor oil concentrations in the range of 3-4% (w/w) did not affect the lag time. With the control of the membrane thickness, the onset of release could be adjusted from 2 to 7 h. The formulations with tL of 3.9 and 5.8 h may have practical benefits in that if such systems are administered simultaneously with conventional forms the 6 and 4 times daily drug dosage frequency would be reduced to 3 and 2 times regimens, respectively. A theoretical justification was provided for the observed nonlinear relationship between the onset and/or tL of drug release and thickness of the semipermeable membrane. After the lag time, the drug release from the systems conformed to the USP requirements.